A Randomized Trial Investigating the Influence of Strength Training on Quality of Life in Ischemic Stroke. Issue 2 (17th February 2016) - Aidar, Felipe José; de Oliveira, Ricardo Jacó; de Matos, Dihogo Gama; Mazini Filho, Mauro Lucio; Moreira, Osvaldo Costa; de Oliveira, Cláudia Eliza Patrocínio; Hickner, Robert C.; Reis, Victor Machado
Abstract: Background : Strength training post stroke is widely acknowledged as an important part of a rehabilitation program. Muscle strength has been shown to be a significant contributor to physical disability after stroke, which in turn has an immense impact on the reintegration of patients into society, affecting their quality of life. Objective : This was a randomized intervention trial to determine the effect of a resistance training program on the quality of life in patients with stroke. Methods : An experimental group (EG), consisting of 11 subjects aged 51.7 ± 8.0 years, and a control group (CG), consisting of 13 subjects aged 52.5 ± 7.7 years, were studied before and after 12 weeks. EG underwent 12 weeks of strength training three times a week. The CG did not undergo strength training during the 12-week study period. Results : There was a significant increase in quality of life from pre-test to post-test (Δ% = 21.47%; p  = 0.021) in EG. There were significant differences in all indicators of quality of life between groups at 12 weeks. There were greater gains in strength in EG than in CG ( p  ≤ 0.05). There was a negative correlation between the strength gains as determined with the 1RM test and the quality of life, especially in lower limb exercises. Conclusion : The results of this study indicate that there was an improvement in the measures of strength in EG, and that there was a correlation between improvements in strength and quality of life in these patients who had previously suffered a stroke at least one year prior to study.